Mechanical Properties Transformation On Zr54Al17Co29 Bulk Metallic Glass by Partial Crystallization - Pradana, Yanuar Rohmat Aji; Jang, Jason Shian-Ching; Setyabudi, Sofyan Arief (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
Study on biomaterials is recently essential for rapid development of medical application and Zr54Al17Co29 BMGbecomes promising candidate due to the lack of toxic elements. Partial crystallization by isothermal annealing at SCL region was used to variate the crystallinities of BMG. The structural and thermal properties of as cast and partially crystallized samples were confirmed by XRD and DSC test, while microvickers and compression test were further utilized to investigate their mechanical properties. By the higher crystallinity, the hardness could be slightly increased in range 540 ± 5 to 575 ± 5 Hv. As-cast sample shows the yield strength and plastic strain of 2130 ± 75 MPa and 2.2 ± 1.6%. The yield strength is increased by the presence of 10% nanocrystal, afterwards, fall and raise phenomena are obtained with further crystallinity. However, with higher crystallinity, the plasticity is significantly degraded and no more plastic strain observed at sample with 50% of crystallinity. Both the presence of nanocrystalline phase and free volume annihilation are the reason of mechanical properties change on the Zr-based BMG.